Integrating experimentation and instrumentation in upper-division physics - Zhang, Qi (Kansas State University, 2009)
Over the past 20 years there have been limited efforts to improve students’ interest and knowledge of electronics and to offer students experiences to integrate and apply their knowledge of electronics with experimental physics. None of the reform efforts cited in the literature have performed a careful assessment of student learning and attitudes, and most of them report anecdotal success. These programs share several commonalities. They typically have a capstone project experience in which students apply their knowledge and skills in electronics and instrumentation to a particular context. The KSU Physics Department has embarked on an endeavor to improve the PMI (Physical Measurement and Instrumentation) class taken by physics majors. Capstone project experiences for students in PMI will provide them with an opportunity to revisit experiments they completed in previous courses. They then apply the knowledge and skills in electronics and instrumentation learned at the beginning of the PMI course to automate these experiments. The use of LabVIEW and NI ELVIS provides a range of opportunities to students due to their visual interface and easy learning curve. However, they do have some disadvantages such as speed and resolution when compared to more traditional measurements with oscilloscopes. Three specific capstone experiences have been developed in PMI. These include saturated absorption in Rubidium, the Franck-Hertz experiment, and the speed of light measurement. In each case, students first complete the traditional experiments and then use NI ELVIS and LabVIEW to automate these experiments. Students are provided minimal explicit guidance in completing the capstone projects. These include one-page handouts describing the goals, basic procedures and questions that students have to answer for themselves. Comparing data from traditional experiments and those from automated using LabVIEW and NI ELVIS provides a context in which to discuss the trade-offs between the traditional and automated experiments. Future efforts include the development of more experiments as well as careful assessment of student learning and attitudes as a result of the capstone experiences in the PMI class. This project can potentially inform similar efforts at other institutions in the future.
Keywords: Labview; advanced lab; Physics, General (0605)